Фонетичні варіанти слів в українській мові (за матеріалами лексикографічних джерел) - Самойлова, І. (Лексикографічний бюлетень, 2016)
The article presents an analysis of phonemic variants of words in accordance with the tendencies of the orthographic norm dynamics. The comparative data analysis in historical and modern lexicographic works, and analysis of the peculiarities of variant forms of words show the changes in the normative status of lexical units. The different types of phonemic variants of words are presented in this paper.